ANTIMICROBIAL AND STRUCTURAL EFFECTS OF DIFFERENT IRRIGATION SOLUTIONS ON GUTTA-PERCHA CONES - Sevinç Aktemur Türker; Hülya Mehtap Aslan; Emel Uzunoğlu; Bahar Özçelik (Istanbul University, 2015)
Purpose: To evaluate the alterations on the surface of gutta-percha cones (GPCs) on exposure to the different irrigation solutions and their possible antibacterial effect against Enterococcus faecalis. (E. faecalis) Materials and Methods: Disinfection ability of different solutions (5.25% sodium hypochlorite, 2% chlorhexidine, 1% peracetic acid, and QMix) were tested with 96 GPCs and the time of exposure to each solution was 5 and10 minutes, respectively. GPCs used in this study were contaminated with E.faecalis. After disinfection, GPCs were placed in tubes containing the medium and incubated at 37˚C for 7 days. All tubes were visually checked for turbidity at 24-hour intervals. About 92 new GPCs were analyzed by means of SEM/EDS to assess the topography and chemical elements present on their surface. The data generated was analyzed using Pearson chi-square test, p<0.05. Results: There were no significant statistical differences in disinfection quality between the irrigation solutions used on GPCs contaminated with E. faecalis (p>0.05). SEM/EDS analyses showed no alteration in the superficial features of GPCs after treating with various irrigation solutions. Conclusion: QMix was found to be an effective agent for rapid disinfection of GPCs as well-known irrigation solutions. Irrigation solutions were found to have sterilized the GPCs after both 5 and 10 minutes of exposure.